Frog music a novel - Donoghue, Emma 1969- (Little, Brown, 2014)
"Emma Donoghue's explosive new novel, based on an unsolved murder in 1876 San Francisco. Summer of 1876: San Francisco is in the fierce grip of a record-breaking heatwave and a smallpox epidemic. Through the window of a railroad saloon, a young woman called Jenny Bonnet is shot dead. The survivor, her friend Blanche Beunon, is a French burlesque dancer. Over the next three days, she will risk everything to bring Jenny's murderer to justice...if he doesn't track her down first. The story Blanche struggles to piece together is one of free-love bohemians, desperate paupers and arrogant millionaires; of jealous men, icy women and damaged children. It's the secret life of Jenny herself, a notorious character who breaks the law every morning by getting dressed: a charmer as slippery as the frogs she hunts. In thrilling, cinematic style, FROG MUSIC digs up a long-forgotten, never-solved crime. Full of songs that migrated across the world, Emma Donoghue's lyrical tale of love and bloodshed among lowlifes captures the pulse of a boomtown like no other"..
Keywords: Geschichte 1800-1900; Historical fiction; FICTION / Crime; FICTION / Family Life; FICTION / General; FICTION / Historical; FICTION / Literary; Women dancers -- Fiction; Murder -- Investigation -- Fiction; San Francisco (Calif.) -- 19th century -- Fiction